How Does a 12-Week Physical Exercise Program Affect the Motor Proficiency and Cognitive Abilities of Overweight and Normal-Weight Preschool Children? - Borko Katanic; Aleksandra Aleksic Veljkovic; Radivoje Radakovic; Nenad Stojiljkovic; Mihai Olanescu; Miruna Peris; Adrian Suciu; Danut Popa (MDPI AG, 2024)
The objective of this research was to examine a 12-week exercise program and its impact on the motor proficiency and cognitive abilities of preschool children with overweight and normal weight. The study involved a total of 71 participants who were preschool children enrolled in a longitudinal study. Body mass index (BMI) was determined by measuring body height and weight, and the nutritional status of the children was assessed using the World Health Organization's (WHO) criteria. Motor proficiency encompasses both motor abilities and motor skills, and the assessment of motor abilities was conducted using subtests from the Bruininks-Oseretsky Test of Motor Proficiency (BOT-2). These subtests measured fine motor integration, manual dexterity, balance, and bilateral coordination. The evaluation of motor skills involved the utilization of the Test of Gross Motor Development (TGMD-2), which examines both locomotor skills and manipulative skills. Cognitive abilities were assessed using the School Maturity Test (TZS). All participants, regardless of weight status, took part in a 12-week physical exercise program. According to the World Health Organization's criteria, 52 children (73.2%) were categorized as having a normal weight, while 19 children (26.8%) were classified as overweight. These findings indicate that every fourth child in the study was overweight. Using a statistical analysis called SPANOVA (2 × 2, group × time), differences were observed in three out of eleven variables. Specifically, there were significant differences in two motor skill variables: manipulative skills (p = 0.006) and total movement skills (p = 0.014). Additionally, there was a significant difference in one cognitive ability variable: visual memory (p = 0.010). No significant differences were found in the remaining variables. The findings of this study aimed to contribute to the understanding of the potential benefits of regular exercise on motor and cognitive development in preschool children, specifically examining the differences between overweight and normal-weight children. By investigating these effects, the study could provide valuable insights for educators, parents, and health professionals involved in promoting the overall well-being of preschool-aged children. Regular physical exercise has been found to have positive effects on motor and cognitive abilities in both overweight and normal-weight preschool children.